An ultra‐compact multimode interference coupler with a subwavelength grating slot. Issue 2 (25th January 2013) - Ortega‐Moñux, Alejandro; Alonso‐Ramos, Carlos; Maese‐Novo, Alejandro; Halir, Robert; Zavargo‐Peche, Luis; Pérez‐Galacho, Diego; Molina‐Fernández, Iñigo; Wangüemert‐Pérez, J. Gonzalo; Cheben, Pavel; Schmid, Jens H.; Lapointe, Jean; Xu, Danxia; et al.
<x xml:space="preserve">Abstract</x> Multimode interference couplers (MMIs) are fundamental building blocks in photonic integrated circuits. Here it is experimentally demonstrated, for the first time, a two‐fold length reduction in an MMI coupler without any penalty on device performance. The design is based on a slotted 2 × 2 MMI fabricated on a commercial silicon‐on‐insulator (SOI) substrate. The slot is implemented with a subwavelength grating (SWG) comprising holes fully etched down to the oxide cladding, thereby allowing single etch step fabrication. The device has been designed using an in‐house tool based on the Fourier Eigenmode Expansion Method. It has a footprint of only 3.5 μm x 23 μm and it exhibits a measured extinction ratio better than 15 dB within the full C‐band (1530 nm‒1570 nm). SWG engineered slots thus offer excellent perspectives for the practical realization of MMIs couplers with substantially reduced footprint yet with outstanding performance. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>